CO2 Sequestration, Biofuels and Depollution[electronic resource] - Lichtfouse, Eric.; Schwarzbauer, Jan.; Robert, Didier; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Water is the driving force of all nature. This old quote from Leonardo da Vinci remind us that without water life is simply not possible. As a consequence, water is probably the most important wealth for humanity. In spite of this, drinking water is still polluted by man-made toxicals gathered by waters in soils and the atmosphere. This book presents advanced methods to clean water and air. Chapters also focus on biofuels, greenhouse gases and genetically modified crops.
1. Chlorine for water disinfection: properties, applications and health effects -- 2. Greenhouse gas from organic waste composting: emissions and measurement -- 3. CO2 photocatalytic reduction: photocatalyst choice and product selectivity -- 4. Fluoride in drinking water: health effects and remediation -- 5. Selenium in agriculture. Water, air, soil, plants, food, animals and nanoselenium -- 6. Biofuels:{u08A9}oethanol, biodiesel, biogas, biohydrogen from plants and microalgae -- 7. Digestion tests to measure heavy metal bioavailability in soils -- 8. Biosafety risk of genetically modified crops containing Cry genes -- 9. Foundry air pollution: hazards, measurements and control -- 10. Lignolytic enzymes for water depollution, coal breakdown, and paper industry.
Keywords: Environment; Renewable energy resources; Renewable energy sources